Pendidikan In-Formal (Keluarga) sebagai Solusi dalam Proses Pembelajaran di Tengah Pandemi Covid-19 - Irma Novayani (STIT Al-Aziziyah, 2021)
This study aims to build children's thinking attitude (character) in the learning process in the midst of the covid-19 pandemic involving parents, family and the community. The research method used is library research method. The results of this study are (1) Parents, fortitude and determination as well as people's patience in providing education to children are the most important and main things in dealing with educational problems in the midst of this covid-19 pandemic (2) Family, basically the education process in the family lasts a lifetime (long life education), as long as family members are still interacting and communicating socially. (3) Community is an effort to change behavior and attitudes in children which aims to increase children's knowledge, skills and awareness of the social values of society.